An Investigation on Compressive Strength of Concrete Blended With Groundnut Shell Ash - Abdul Wahab Abro; Aneel Kumar; Manthar Ali Keerio; Zubair Hussain Shaikh; Naraindas Bheel; Ali Aizaz Dayo (NAROTAMA UNIVERSITY, Indonesia, 2021)
Concrete is frequently utilized infra-structural construction material all over the world. Cement is the main part of the concrete, during its manufacturing emission of gases such as carbon dioxide (CO2) from cement factories create greenhouse effect. In these days various natural pozzolanic materials are used as partial replacement of cement to enhance strength and durability and to reduction in consumption of cement consequently reduction in carbon dioxide (CO2) emission. The aim of this research is to investigate the effect of groundnut shell ash as a cement replacement material on workability and compressive strength of concrete. One mix of ordinary concrete and five mixes of modified concrete were prepared, where cement is replaced by groundnut shell ash from 3% to 15% by weight of cement, with 3% increment with 1:2:4 binding ratio mixed with 0.5 water/cement ratio. The workability and compressive strength of concrete was investigated. The obtained outcomes demonstrated that, groundnut shell ash as a cement replacement material have significant effect on compressive strength of concrete.